Antimicrobial Efficacy of Caprylyl Glycol and Ethylhexylglycerine in Emulsion - Lawan, Kunlayakorn; Kanlayavattanakul, Mayuree; Lourith, Nattaya (Journal of Health Research, 2018)
Antimicrobial efficacies of caprylyl glycol and ethylhexylglycerin in an emulsion were evaluated by USP24-NF19. The minimum concentration of caprylyl glycol and ethylhexylglycerin inhibited Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa and Candida albicans within 1 day and Aspergillus niger within 28 days was 0.5% and 1.5%, respectively. The 1:3 mixture ratio of the caprylyl glycol and ethylhexylglycerin was chosen for further steps on inhibitory effect towards those prohibited microbial in cosmetics by evaluation at the concentration of 0.5%, 1.0%, 1.5% and 2.0%, respectively. It was found that the minimum concentration inhibited S. aureus within 3 days, E. coli, P. aeruginosa and C.albicans within 1 day and A. niger within 28 days was 1.0%. This developed preservative system offers multifunctional cosmetic ingredients in addition to their emollient efficacies.